Resolving of optimal fractional PID controller for DC motor drive based on anti-windup by invasive weed optimization technique - Badriyah Ahmed Obaid; Ameer Lateef Saleh; Abbas Kareem Kadhim (Institute of Advanced Engineering and Science, 2019)
This paper exhibits a design procedure for tuning the parameters of Fractional Order Proportional Integral Derivative (FOPID) P controller to optimize the DC motor drive operation. The optimization technique is establishing on Invasive Weed Optimization (IWO). This paper also proposes the use of anti-windup aspect to against the saturation which may occur in the FOPID controller. The objective of this design is to improve the performance of the drive subjected to different transient response and loading conditions. A comparative study is carried out with a classical PID controller. The Matlab simulation results show more improvements in the proposed system.